2018
DOI: 10.1016/j.icarus.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

PRIMASS visits Hilda and Cybele groups

Abstract: The Cybele and Hilda dynamical groups delimit the outer edge of the asteroid belt. Their compositional distribution is a key element to constrain evolutionary models of the Solar System. In this paper, we present a compositional analysis of these populations using spectroscopic observations, SDSS and NEOWISE data. As part of the PRIMASS (Primitive Asteroids Spectroscopic Survey), we acquired visible spectra of 18 objects in Hilda or Cybele groups with the Goodman High Throughput Spectrometer at the 4.1m SOAR t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
0
21
2
Order By: Relevance
“…These similarities suggest that the JTs also have a primitive nature, having under- gone little to no thermal alteration since their formation. Further investigations revealed a bimodality in their color distribution both in visible and NIR wavelengths, with one "red" peak related to the D-types, and one less red peak, similar to P-types (Emery et al, 2010;Wong et al, 2014;De Prá et al, 2018). This bimodality has been interpreted as the predominance of two intrinsically different compositional groups.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These similarities suggest that the JTs also have a primitive nature, having under- gone little to no thermal alteration since their formation. Further investigations revealed a bimodality in their color distribution both in visible and NIR wavelengths, with one "red" peak related to the D-types, and one less red peak, similar to P-types (Emery et al, 2010;Wong et al, 2014;De Prá et al, 2018). This bimodality has been interpreted as the predominance of two intrinsically different compositional groups.…”
Section: Introductionmentioning
confidence: 91%
“…Vilas (1995) suggested that it could be related to hydrated materials in the surface of the asteroid. We characterized the turnover region following the methodology described in De Prá et al (2018); the turn-off point was measured by calculating the furthest point from a linear fit considering just the edges of the spectrum. In addition to the turn-off wavelength, we also measured the slope of the drop-off in reflectance on wavelengths lower than the turn-off point (near-UV slope).…”
Section: Donaldjohansonmentioning
confidence: 99%
“…A common feature observed in several of these objects across the asteroid belt is the 0.7 µm absorption band, characteristic of hydrated minerals (Vilas 1994;Carvano et al 2003;Fornasier et al 2014). The number of objects presenting this feature peaks at the central belt and decreases at the Cybele region, delimiting the hydration zone (Rivkin 2012;Fornasier et al 2014;De Prá et al 2018). As part of the PRIMitive asteroid spectroscopic survey (PRIMASS), we studied the visible spectroscopy of eight primitive asteroids families in the inner belt and identified a mix of anhydrous and hydrated families in that region, where the percentage of hydrated members in a family can reach nearly 80% (de León et al 2016;Morate et al 2016Morate et al , 2018Morate et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…We are confirming, using near-infrared photometry combined with NEOWISE and SDSS data, some results already known for several families. Vesta shows a small contamination of rocky and primitive asteroids (Licandro et al 2017); Nysa-Polana presents a bimodality in its composition corresponding to the presence of two families (Cellino et al 2001;Walsh et al 2013;Milani et al 2014;Dykhuis & Greenberg 2015); Eos is the only K-type family identified in the inner belt (Mothé-Diniz et al 2005; and Hilda shows some bimodality inside the primitive region (De Prá et al 2018). In addition, we found relevant results in our analysis related to the Ino and Baptistina families.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Hilda family, located within the Hilda dynamical group, the combination that minimizes the KS-test results is a 36-64% of P1-P2 populations. De Prá et al (2018) reported a primitive surface composition with a bimodal distribution. This is in agreement with our results.…”
Section: Some Primitive Familiesmentioning
confidence: 99%